Sharing Archaeological Knowledge: The Interactive Reporting System. (4th July 2021) - Derudas, Paola; Dell'Unto, Nicolò; Callieri, Marco; Apel, Jan
ABSTRACT: This study describes the development of a digital reporting system designed to provide archaeologists with a dynamic and interactive 3D web platform that can be used for describing in great detail records and activities undertaken across a multi-year field investigation campaign. The system was used to compose the archaeological report of a multi-year investigation and employed during the pandemic crisis for supporting digital courses in archaeological practice; the paper also reports the preliminary results of the use of this platform within teaching activities. Unlike other web solutions, this system supports an assisted publication of archaeological contents that integrates a 3D visualization system in the reporting process, exploiting the communicative potentials of 3D models and the web. This study represents a contribution to research on sustainable forms of management and publication of archaeological contents and their reuse and sharing.